The badness of discrimination - Lippert-rasmussen, KASPER (Ethical theory and moral practice, 2006)
The most blatant forms of discrimination are morally outrageous and very obviously so; but the nature and boundaries of discrimination are more controversial, and it is not clear whether all forms of discrimination are morally bad; nor is it clear why objectionable cases of discrimination are bad. In this paper I address these issues. First, I offer a taxonomy of discrimination. I then argue that discrimination is bad, when it is, because it harms people. Finally, I criticize a rival, disrespect-based account according to which discrimination is bad regardless of whether it causes harm.